Calcium State-Dependent Regulation of Epithelial Cell Quiescence by Stanniocalcin 1a - Li, Shuang; Liu, Chengdong; Goldstein, Allison; Xin, Yi; Ke, Caihuan; Duan, Cunming (Frontiers in Cell and Developmental Biology, 2021)
The molecular mechanisms regulating cell quiescence-proliferation balance are not well defined. Using a zebrafish model, we report that Stc1a, a secreted glycoprotein, plays a key role in regulating the quiescence-proliferation balance of Ca2+ transporting epithelial cells (ionocytes). Zebrafish stc1a, but not the other stc genes, is expressed in a Ca2+ state-dependent manner. Genetic deletion of stc1a, but not stc2b, increased ionocyte proliferation, leading to elevated body Ca2+ levels, cardiac edema, body swelling, and premature death. The increased ionocyte proliferation was accompanied by an increase in the IGF1receptor-mediated PI3 kinase-Akt-Tor signaling activity in ionocytes. Inhibition of the IGF1 receptor, PI3 kinase, Akt, and Tor signaling reduced ionocyte proliferation and rescued the edema and premature death in stc1a-/- fish, suggesting that Stc1a promotes ionocyte quiescence by suppressing local IGF signaling activity. Mechanistically, Stc1 acts by inhibiting Papp-aa, a zinc metalloproteinase degrading Igfbp5a. Inhibition of Papp-aa proteinase activity restored ionocyte quiescence-proliferation balance. Genetic deletion of papp-aa or its substrate igfbp5a in the stc1a-/- background reduced ionocyte proliferation and rescued the edema and premature death. These findings uncover a novel and Ca2+ state-dependent pathway regulating cell quiescence. Our findings also provide new insights into the importance of ionocyte quiescent-proliferation balance in organismal Ca2+ homeostasis and survival.